Proud to Bugis: Understanding Faith and the Moral Emotions of The Bugis Community in The Culture of Siri’ Na Pesse - Elka Anakotta; Flavius Floris Andries; Hoang Thi Hue (Al-Albab, 2025)
This paper examines how the moral emotions, i.e. pride and shame, are formed and manifested within the Bugis community’s Siri’ culture, especially through its three main values: sipakatau, sipakainge, and sipakalebbi. In sipakatau, the status of the person is dominant, and personal dignity and honor are maintained. According to sipakatau, the spirit of reciprocal respect between human beings known as sipakainge comes out. Moreover, in sipakalebbi, respect and appreciation are the basis of advising and reminding each other, so that the life of the community is in harmony.  These three values are an inseparable unity in the Siri’ culture that is maintained in the Bugis communal life, which creates the moral emotions of pride and shame. Pride is the ethical feeling that forms the foundation of self-awareness of a person to appreciate himself (sipakatau), which in turn forms the foundation of the Bugis community in establishing harmonious interpersonal relations. Personal dignity affects the respect of others, which is expressed in harmonious and equal social relations.  Shame, guilt, and embarrassment are the forces that work together with the realization of pride in sipakatau, sipakainge, and sipakalebbi. The moral emotions of shame, guilt, and embarrassment become integrated as mechanisms to safeguard pride as a Bugis person, ensuring that the pride of being Bugis is internalized throughout an individual’s life.